The Right Person for the Right Job: Workers' Prosociality as a Screening Device - Maria Bigoni; Matteo Ploner; Thi-Thanh-Tam Vu (Institute of Labor Economics (IZA), 2021)
The impact of workers' non-pecuniary motivation on their productivity is a fundamental issue in labor economics. Previous studies indicate that prosocially motivated workers may perform better when assigned to jobs having socially desirable implications – even if effort is non contractible and they are offered a low-powered fixed-compensation scheme – as compared to a standard job with an effort-contingent payment. This suggests that profit maximizing employers should assign workers to different jobs, based on workers' prosociality. We run an experiment to explore the link between workers' prosociality and their level of effort under a prosocial and a standard job, and show that employers actually exploit the information on workers' prosociality to assign them the type of job that would be most profitable from the firm's perspective.
Keywords: C91; D63; D64; 330; dictator game; incentives; laboratory experiment; principal-agent game; real-effort task